Curva de crescimento e marcha de absorção de macronutrientes em três cultivares de amoreira (Morus alba L) - do Vale, Diego Wyllyam [UNESP]; Prado, Renato de Mello [UNESP]; Gondim, Ancelio Ricardo Oliveira [UNESP]; Takahashi, Roque [UNESP]; Correia, Marcus Andre Ribeiro [UNESP] (Soc Chilena Ciência Suelo, 2009)
To evaluate the growth and pattern of nutrient absorption (N, P, K, Ca, Mg and S amongst others) in three berry cultivars (treatments), four plants by treatment in different phonological stages were harvested. The experiment was arranged in randomized design of factorial 3x5 with three replicates. There cultivars were used FM Shima-Miura, IZ 56/4 and Miura and above ground biomass was harvested in five occasions 45, 60, 75, 90 and 115 days after plantation. It was observed that the accumulation of nutrients presented different pattern and cv. IZ 56/4 was superior compared with PM Shima-Miura for N, P, K, Ca, Mg and S and N, P, K and S for Miura. For example, the accumulation of N expressed on mg plant"(1) per berry plant cultivar PM Shima-miura, IZ 56/4 and Miura was respectively 4,21; 8,14 and 5,56, for K 2,71; 5,22 and 2,64 and for Ca 2,47; 4,52 and 3,59.
Growth curve and macronutrient uptake in three berries (Morus alba L) cultivars
Keywords: Mineral nutrition; uptake rate; nutritional requirements; Morus alba L.